EXCELLENT RESPONSE TO ALECTINIB IN ALK-POSITIVE NSCLC ADENOCARCINOMA-A CASE REPORT AND LITERATURE REVIEW - Ismaili, Irfan; Stojchevska, Vesna Pachoska; Janev, Olivera Gjeorgjieva (Journal of Morphological Sciences, 2023)
Non small cell lung carcinoma (NSCLC) is a type of lung carcinoma that slowly grows within the lung tissue, thus it is often diagnosed lately when the disease has already progressed and passed to other body organs and/or lymph nodes. This makes NSCLC in most of the cases inoperable at the exact moment of diagnosing, which leads to a necessity of using a chemotherapy that has the purpose of narrowing the extended masses in the lungs and/or near/further metastases. Alectinib is a tyrosine- kinase inhibitor (TKI) that is currently being used as a first line target therapy in treating the inoperable ALK rearranged NSCLC, but still the effectiveness of the treatment is not definitely known and examined. Herein, we report a case of a 51-year-old male patient presented to our hospital with hemoptysis for 2 weeks. Contrast-enhanced computerized tomography (CT) of the chest showed an approximately 28x23 mm soft tissue mass infiltrating into the lumen of the right bronchus and causing obstruction. On the same side at the base, a hypodense nodule of 19 mm with some surrounding pneumonic reaction and irregular contours was detected. Several significant lymph nodes were detected in the hilar and mediastinal regions. Transobronchial biopsy of the mass showed pulmonary adenocarcinoma and immunohistochemical testing results confirmed ALK rearrangements. TKI alectinib was given at a dosage of 600mg twice per day for 13 cycles, achieving a complete response of the disease with complete regression of the mass in the right bronchus, complete regression of the right nodule and hilar and mediastinal lymph nodes were not detected after treatment . The patient continued to receive alectinib and did not report any specific discomfort at his 13 month follow-up. Keywords: NSCLC, Lung adenocarcinoma, ALK rearrangement, TKIs, Alectinib